Melodic Intonation Therapy for Post-stroke Non-fluent Aphasia: Systematic Review and Meta-Analysis - Haro-Martínez, Ana; Pérez-Araujo, Carmen M.; Sanchez-Caro, Juan M.; Fuentes, Blanca; Díez-Tejedor, Exuperio (Frontiers in Neurology, 2021)
Introduction: Melodic Intonation Therapy (MIT) is one of the most studied speech and language therapy (SLT) approaches for patients with non-fluent aphasia, although the methodological quality of the studies has been rated as low in previous reviews. Aim: to update current evidence on the possible efficacy of MIT for the treatment of non-fluent post-stroke aphasia. Methods: A systematic review and meta-analysis. We selected randomized clinical trials (RCT) that included adult patients over 18 years of age with non-fluent post-stroke aphasia, whose intervention was MIT vs. no therapy or other therapy. We excluded non-RCT, mixed populations including patients with aphasia of non-stroke etiology, no availability of post-stroke aphasia-specific data, and incomplete studies. Three sections of communicative ability were analyzed as outcomes: functional communication, expressive language (naming and repetition) and comprehension. Results: We identified a total of 4 eligible RCTs involving 94 patients. Despite the heterogeneity in the psychometric tests employed among the trials, a significant effect of MIT on functional communication (evaluated by the Communication Activity Log) was found (SMD 1.47; 95% CI 0.39 to 2.56). In addition, a positive effect of MIT on expressive language (repetition) was found (SMD 0.45; 95% CI 0.01 to 0.90). No significant effects on comprehension measurements were found, despite a lack of significant statistical heterogeneity. Conclusion: This systematic review and meta-analysis shows a significant effect of MIT on improving functional communication and on repetition tasks. Future larger RCT specifically addressing those outcomes should provide the definite evidence on the efficacy of MIT on post-stroke aphasia recovery. Registration:PROSPERO-URL https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=144604